Triglyceride-glucose index and the progression of chronic obstructive pulmonary disease, panvascular disease, and multimorbidity: a prospective cohort study - Shuo Zhang; Xiaotian Li; Jiajing Li; Siwei Xie; Zongbin Wang; Zhijie Zheng; Jie Huang; Shuduo Zhou (Frontiers in Cardiovascular Medicine, 2026)
Objective Chronic obstructive pulmonary disease (COPD) and panvascular disease (PD) are often driven by shared risk factors. We aimed to investigate the longitudinal association of triglyceride-glucose (TyG) index with incidence of COPD, PD, and their multimorbidity. Methods Our study used data from the UK Biobank, a population-based prospective study. Cox proportional hazards regression was used to evaluate the association between TyG index and the risk of incident COPD, panvascular disease, and their Multimorbidity. Multistate models (MSMs) were used to evaluate the longitudinal progression from healthy to incident COPD or PD, and ultimately to multimorbidity, across TyG index quartiles. Results Among the 296,818 participants included in the final analysis, the TyG index was associated with higher incidence of COPD and PD. Each 1-SD increase in TyG index was associated with a 9% higher risk of PD (HR 1.09, 95% CI 1.05–1.12). These associations were more pronounced among females. In multistate analyses, compared with the lowest quartile, women in the highest TyG quartile had greater risks of progression from baseline to COPD (HR 1.22, 95% CI 1.04–1.43), baseline to PD (HR 1.29, 95% CI 1.19–1.39), COPD to multimorbidity (HR 2.11, 95% CI 1.32–3.37), and PD to multimorbidity (HR 3.67, 95% CI 2.00–6.72). For males, a higher TyG index was protective against COPD incidence (HR 0.79, 95% CI 0.68–0.93) but increased PD risk (HR 1.18, 95% CI 1.09–1.26), whereas no significant associations were found for other transitions. Conclusions Elevated TyG index was associated with incident COPD and PD, while the association with multimorbidity was attenuated after full adjustment in the overall cohort. In multistate analyses, stronger and more consistent associations were observed in women, particularly for progression from single disease to multimorbidity. The TyG index may serve as a metabolic indicator that helps identify women at elevated risk and may inform targeted prevention strategies.